Solvent Effect on Base-Free Synthesis 4-Substituted 2-Oxazolines via Intramolecular Cyclodemesylation - Dalkılıç, Erdin; Güneş, Yakup (Synlett, 2023)
In this present study, the solvent effect was examined for the synthesis of 2-oxazolines via intramolecular cyclodemesylation. To determine the solvent effect, aprotic/protic polar and nonpolar solvents were screened and polar protic solvents met the best result. The remarkable feature of this synthesis is that cyclization takes place in the absence of any base or reagent, in high yields (89–96%). As a result, a series of 4-substituted chiral 2-oxazolines were successfully synthesized through a four-step process, with overall yields reaching between 79% and 88% in a greener approach.
Keywords: solvent effect; green chemistry; heterocycles; intramolecular cyclization; 2-oxazoline